Analisis Kadar Ureum dan Kreatinin pada Pasien Rawat Jalan Diabetes Melitus Tipe 2 - Ria Liftyowati; Retno Widowati; Yeremiah Rubin Camin (FORIKES, 2022)
Diabetes mellitus requires regular monitoring of glycemic control, and if not controlled complications can arise, one of which is kidney damage. This study was conducted to determine the relationship between age, sex and duration of suffering with urea and creatinine levels, and to obtain rates of increase in urea and creatinine levels as duration of suffering increases. The subjects of this study were 43 patients who were recorded in the medical records of patients diagnosed with type 2 DM from internal medicine polyclinics, who were selected by purposive sampling technique. The results of the regression test showed that there was a relationship between duration of suffering from type 2 DM with urea and creatinine levels. There was an increase in urea levels of 92.239 mg/dL, and creatinine of 5.495 mg/dL with increasing duration of suffering.Keywords: diabetes mellitus type 2; creatinine; urea ABSTRAK Diabetes melitus memerlukan pemantauan kontrol glikemik secara teratur, dan jika tidak terkontrol dapat timbul komplikasi yang salah satunya adalah kerusakan ginjal. Penelitian ini dilakukan untuk mengetahui hubungan antara usia, jenis kelamin dan lama menderita dengan kadar ureum dan kreatinin, dan untuk memperoleh angka peningkatan kadar ureum dan kreatinin seiring bertambahnya lama menderita. Subyek penelitian ini adalah 43 pasien yang tercacat dalam data rekam medis pasien yang terdiagnosis DM tipe 2 dari poli penyakit dalam, yang dipilih dengan teknik purposive sampling. Hasil uji regresi menunjukkan adanya hubungan antara lama menderita DM tipe 2 dengan kadar ureum dan kadar kreatinin. Terjadi peningkatan kadar ureum sebesar 92,239 mg/dL, dan kreatinin sebesar 5,495 mg/dL seiring bertambahnya lama menderita.Kata kunci: diabetes mellitus tipe 2; kreatinin; ureum